PENGARUH FIRM SIZE, LABA RUGI, OPINI AUDITOR TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Siti Tiffanny Guci; Rosiana Clarita; Mellisa ,; Jimmy Ronaldo; Wilbert Howard; Ricardo ,; Isna Asdiani Nasution (Universitas Islam Islam Sumatera Utara, 2019)
The financial report has an important role in the survival of a company, the report is based on Bapepam Regulation No. X.K. 2, appendix to the Decree of the Chairman of Bapepam-No. KEP-36/PMK/2003 concerning Report Submission Obligations Periodic Financial,